Banheiros residenciais construídos para pessoas com deficiência e sua acessibilidade pela ótica de seus usuários - Janaina Scaramussa dos Santos (2012)
The emphasis of this research study is on experiences that people with disabilities or people with reduced mobility have about usability of their residential bathroom. Those users make improvised design solutions to suit their needs. The analysis includes flaws of usability of distinct spatial configurations and the inventiveness users developed to solve such problems. The data collection took place in private adapted bathrooms. In such cases, the residential environment had been originally constructed without addressing concerns for accessibility of users with disability. Thebathroom, as compared to the other rooms of each home, is usually smaller. In spite of that it serves as storage for a variety of items, objects and functions, especially in regards to the collective use of such space. There are clearly accessibility flexibility and safety related issues in those bathrooms created by people with disabilities or reduced mobility and that affects the relationship of dependence among users in home environment. The central question refers to understanding attitudes of users and industry professionals, which may be favorable to installation of accessibility elements in adapted residential bathrooms. The aim is to investigate bathrooms that have been renovated or adapted for people with disabilities or reduced mobility, while assessing the quality of adopted accessibility solutions, and the impact of such design solutions as ways to empower users, and shift the perspective of the real estate market towards more user friendly environments. The research tasks arecategorized in three stages: (a) survey preparation and sampling of volunteers, (b) interviewing with questionnaires, photographs and informal conversation, (c) transcripting data, along with designing of graphic representation of the material. Results indicate that users do not see accessibility and universal design application as a goal in designing their home bathrooms. Users focus on finding out affordable solutions that are distant from implementation of required design standards.